2011
DOI: 10.1590/s0074-02762011000300001
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus type 4 arrives in the state of Rio de Janeiro: a challenge for epidemiological surveillance and control

Abstract: EditorialDengue virus type 4 arrives in the state of Rio de Janeiro: a challenge for epidemiological surveillance and control Dengue virus type 4 (DENV-4) re-emerged in the state of Roraima (RR), a remote state in the extreme Northwest of Brazil, in July 2010 at the height of the rainy season. This serotype had not been detected in the country for almost 30 years, when DENV-4 and DENV-1 caused a limited outbreak in RR's capital city Boa Vista in [1981][1982] with 11,000 reported cases. The reinvasion of DENV-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 0 publications
2
50
0
2
Order By: Relevance
“…The absolute number of infections was greater, and most strikingly, the annual pattern of epidemics changed, with more severe biennial epidemics being observed. This pattern of biennial epidemics more closely resembles the observed multi-annual cycle of dengue epidemics in endemic countries, including the pattern observed in Brazil (Nogueira et al 2007, Nogueira & Eppinghaus 2011. In agreement, other studies have shown the importance of the parameters related to the vector-host interaction, including the biting rate, in determining the seasonal and multi-annual cycle of dengue (Hay et al 2000, Bartley et al 2002.…”
Section: Mosquito Population Dynamicssupporting
confidence: 88%
“…The absolute number of infections was greater, and most strikingly, the annual pattern of epidemics changed, with more severe biennial epidemics being observed. This pattern of biennial epidemics more closely resembles the observed multi-annual cycle of dengue epidemics in endemic countries, including the pattern observed in Brazil (Nogueira et al 2007, Nogueira & Eppinghaus 2011. In agreement, other studies have shown the importance of the parameters related to the vector-host interaction, including the biting rate, in determining the seasonal and multi-annual cycle of dengue (Hay et al 2000, Bartley et al 2002.…”
Section: Mosquito Population Dynamicssupporting
confidence: 88%
“…Another limitation was the lack of reliable information in each time period on the specific incidence rates for each serotype (among the circulating serotypes) 36 . Some authors claim that the entry of a new serotype into a non-immune population entails a risk of explosive epidemics, even while the succession of serotypes can result in epidemics with more severe cases 10,18,37 . The role of the exposed human populations, the effect of immunity to the virus in the at-risk population, and infestation by the mosquito vector are decisive factors in maintaining the virus in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In RJ, the first DENV-4 cases that were detected occurred in the Cafubá neighbourhood. Cafubá is located in the oceanic region of the municipality of Niterói which is located in the metropolitan region of RJ, Brazil (Nogueira & Eppinghaus 2011). The entomological surveillance of DENV in adult and immature mosquito stages is an important tool for the early prediction of dengue epidemics.…”
mentioning
confidence: 99%
“…The first two confirmed cases were two sisters who lived in the Cafubá neighbourhood of Niterói. Both experienced an onset of symptoms on March 6 2011 (Nogueira & Eppinghaus 2011). We investigated nine other suspected cases of individuals who experienced an onset of symptoms from March 23 2011-April 11 2011 and who lived in Cafubá, São Francisco, São Domingos and Engenho do Mato (Fig.…”
mentioning
confidence: 99%